Public debt and economic growth - The case on Republic of North Macedonia. - Trpeski, Predrag; Kozheski, Kristijan; Cvetanoska, Marijana; Merdzan, Gjunter (Faculty of Economics, Univeristy of Sarajevo, 2020)
Establishing and maintaining macroeconomicstability and fiscal discipline on the one hand, and stimulatingeconomic activity, by enhancing the quality of public finances,increasing capital expenditures, and enhancingcompetitiveness in the Macedonian economy, on the otherhand, are two opposing objectives that should be pursued bypolicymakers. Government borrowing, especially foreignborrowing, is an important source of fixed assets to coverpublic expenditure. However, the sustainability of public debtdepends not only on the level of public debt, but also on thestructure and successful implementation of policies to boosteconomic growth. Borrowing for a country with low economicpotential and a constant shortage of capital is inevitable,especially external borrowing. However, the structure,purpose of the assets and their multiplier effect on the overalleconomy are the main criteria for assessing the impact ofpublic debt on the economy. This paper attempts to apply theeconometric VAR analysis to examine the correlation andcausal relationship between public debt and economic growthrate of the case of the Republic of North Macedonia for theperiod 2002 - 2017. The variables to be analyzed are: GDPgrowth per capita, Public debt as a proportion of GDP, GrossDomestic Investment, Interest Rate and Government Spending.For the purpose of this analysis, a Granger causality test hasbeen conducted. The test results indicate that the impact ofpublic debt growth in North Macedonia does not have asignificant impact on GDP growth per capita. The other testthat is being conducted is a Vector Error Correction Modelwhich shows that public debt is negatively correlated withshort run and long run economic growth.
Keywords: economic growth; GDP per capita; Grangercausality; North Macedonia; public debt